Effect of the varicella vaccination implementation on the development of herpes zoster in children and adolescents - Esma, Inan Yuksel; Asude, Kara Polat; Muge, Gore Karaali; Ayse Esra, Koku Aksu; Mehmet Salih, Gurel (Wiley, 2021)
Herpes zoster (HZ) is an infectious disease caused by latent varicella-zoster virus reactivation. There are conflicting reports on the varicella vaccine's effect on the incidence of HZ in children and adolescents. This study aimed to determine the impact of the single dose of varicella vaccination on HZ prevalence during childhood and adolescence. The study included children and adolescents aged <18 years who presented to the dermatology outpatient clinic between 2005 and 2019 and were diagnosed with HZ. Considering that the universal vaccination program started to be implemented in Turkey in 2013, non-vaccinated cases in the prevaccination period, vaccinated cases in the postvaccination period, and non-vaccinated patients in the postvaccination period were compared in terms of HZ prevalence and demographic features. After the initiation of the varicella vaccination program, the prevalence of HZ was found to decrease by 24.7% in all. The HZ prevalence was significantly reduced in vaccinated children, while the rate of decrease in non-vaccinated children was low (58.6% and 16.4%, respectively). The median age of the non-vaccinated cases in the postvaccination period (10 [min 0.5-max 17] years) was significantly higher compared to the other groups (p < 0.001). The number of cases aged <2 years was the highest in the vaccinated group (p < 0.001). Administration of a single dose of varicella vaccine was insufficient to decrease the prevalence of HZ <18 years of age. In the post-vaccination period, the frequency of HZ in unvaccinated cases increased in adolescence. In vaccinated children, HZ seems to develop at an earlier age.
Keywords: herpes zoster (shingles; VZV); pediatric dermatology; vaccine; varicella